Immunological Link Between Primary Graft Dysfunction and Chronic Lung Allograft Rejection - Bharat, Ankit; Kuo, Elbert; Steward, Nancy; Aloush, Aviva; Hachem, Ramsey; Trulock, Elbert P.; Patterson, G. Alexander; Meyers, Bryan F.; Mohanakumar, T. (The Annals of thoracic surgery, 2008)
Primary graft dysfunction (PGD) in the immediate post–lung transplant period strongly increases the risk of chronic rejection (broncholitis obliterans syndrome). Here, we hypothesized that PGD-induced inflammation augments alloimmunity, thereby predisposing to broncholitis obliterans syndrome. Primary graft dysfunction and broncholitis obliterans syndrome were diagnosed according to the established International Society for Heart and Lung Transplantation criteria. Anti–human leukocyte antigen (HLA) alloantibodies were analyzed using Flow-PRA. Donor HLA class II–specific T cells were analyzed using interferon (IFN)-γ ELISPOT. Serum levels of 25 cytokines and chemokines were measured using LUMINEX. Of the 127 subjects, 29 (22.8%) had no PGD (grade 0), 42 (33.2%) had PGD-1, 36 (28.3%) had PGD-2, and 20 (15.7%) had PGD-3. Patients with PGD grades 1 to 3 (PGD 1-3) had elevated proinflammatory mediators MCP-1, IP-10, interleukin (IL)-1β, IL-2, IFN-γ, and IL-12 in the sera during the early posttransplant period compared with patients with PGD grade 0 (PGD 0). On serial analysis, PGD 1-3 patients revealed increased development of de novo anti-HLA-II (5 years: 52.2% versus PGD 0 13.5%, p = 0.008). However, no difference was found in anti-HLA-I alloantibody development (PGD 1-3 patients 48% versus PGD 0 39.6%, p = 0.6). Furthermore, PGD 1-3 patients had increased frequency of donor HLA class II–specific CD4 + T cells [(91.4 ± 19.37) × 10 −6 versus (23.6 ± 15.93) × 10 −6, p = 0.003]. Primary graft dysfunction induces proinflammatory cytokines that can upregulate donor HLA-II antigens on the allograft. Increased donor HLA-II expression along with PGD-induced allograft inflammation promotes the development of donor specific alloimmunity. This provides an important mechanistic link between early posttransplant lung allograft injury and reported association with broncholitis obliterans syndrome.